Analisis perencanaan dan pengadaan guna menjamin ketersediaan obat di rumah sakit - Rafiastiana Capritasari; Dwiky Ramadhani Kurniawati (Universitas Mataram, 2021)
Management of drug is one of the factors which contribute to the quality of hospital services. This study aimed at finding out drug planning in Pharmacy Unit of Adelia Surgical Hospital by using ABC analysis method. This research is qualitative descriptive study involving informants. Primary data were collected by interview with respondents and secondary data report of general drugs purchased period of May 2018 – May 2019. The Result using ABC analysis indicate that there are 23 (17,42%) kindof drugs in group A, 35 (26,52%) in group B and 74 (56,06%) in grup C. Group A if in the event of an excess or deficiency will couse harm to the hospital. ABC analysis method will effectively improve hospital drug consumption plan.